Queremos comida, quem vai dar? o motim de 1983 contra a fome e o desemprego em São Paulo - Silva, Matheus da (2018)
The objective of this research is to understand the demonstration organized by a mass of unemployed people in Santo Amaro, São Paulo between April 4th and 6th, 1983. The protest was a direct, unorganized, heterogeneous, violent action from the point of view of tactics of struggle and based on causes considered legitimate, which contributed to the demonstration of the unemployed to demonstrate logic; in short , a movement against the military dictatorship. Although in 1983 there was a process of political openness and a serious economic crisis, there were several reactions in civil society and political power. In this way, we also tried to talk about the Civilian Police Dossier and the indictment of those accused of participating in the demonstrations, as well as the representations elaborated in the news “Folha de São Paulo and Estado de São Paulo”, analyzing all the sections and issues of April 1983. As for the representations, we note the predominance of inconvenient and unchanging arguments about protest, as well as associations of it with social disorder. So, we hope to understand the practices and experiences of struggle of a marginalized social group, the political significance of the action and the reason for the elaborated representations about the manifestation and its evidences